China's elite politics : political transition and power balancing - Bo, Zhiyue (Series on contemporary China, 2007)
China?s Elite Politics provides a new theoretical perspective on elite politics in China and uses this theoretical perspective to explain power transfer from Jiang Zemin to Hu Jintao and political dynamics between different factional groups since the Sixteenth Party Congress of November 2002. It explains the transition in structural terms, presents characteristics of China?s political elites, and analyzes the balance of power among formal institutions as well as among factional groups. It also examines political interactions between Jiang Zemin and his cronies on the one side and Hu Jintao and.